ANALISIS SEMIOTIK: MEMAHAMI NILAI MULTIKULTURALISME DALAM LIRIK LAGU “SABILULUNGAN” KARYA KOKO KOSWARA - Nashih, Abdullah Ali; Mu’tazza, Ma’bad Fathi; Kambali, Kambali (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2023)
This article examines the meaning of loneliness in the lyrics of the song "Sabilulungan" by Koko Koswara through Roland Barthes' semiotic analysis. The meanings expressed are denotation, connotation and myth. In this study, Roland Barthes' semiotic theory is used to explain the denotation, connotation and myth of the meaning of "Gotong-Royong" contained in the song's lyrics. The aim of this research is to look for multicultural values ​​in the lyrics of the song "Sabilulungan". This research uses an interpretive qualitative method or inductive way of thinking, namely a way of thinking from the specific to the general. The results of a semiotic study of the lyrics of the song "Sabilulungan" are as follows. The detonating meaning of these lyrics is the author's desire to invite fellow humans to work together. The connotation is that the author feels a sense of empathy for the surrounding environment, especially the diverse cultures in Indonesia, so that they can live in harmony and build unity. The meaning of the myth is that the creator of the song wants to convey that mutual cooperation does not always start with other people, but starts with oneself and invites other people.